Polysaccharide-mediated green synthesis of silver nanoparticles from Sargassum siliquosum J.G. Agardh: Assessment of toxicity and hepatoprotective activity - Ross D. Vasquez; Jovencio G. Apostol; Joshua D. de Leon; Jonathan D. Mariano; Chriselle Marie C. Mirhan; Samuel S. Pangan; Alyssa Gail M. Reyes; Emmanuel T. Zamora (Elsevier, 2016)
The current investigation aimed to determine the toxicity and hepatoprotective potential of silver nanoparticles (AgNPs) synthesized rapidly using sulfated polysaccharide extract from Sargassum siliquosum, a brown alga. The nanoparticles were characterized by UV-visible spectroscopy (UV-vis), scanning electron microscopy (SEM), fourier transform infra-red spectroscopy (FTIR), energy dispersive X-ray (EDX) alongside zeta potential measurement. SPR indicated prominent peaks at 420-460 nm. SEM and DLS showed that biosynthesized AgNPs were in the size range of 20-480 nm and 19.5±6 nm to 471.7±189.4 nm respectively. EDX spectrum indicated strong signal for AgNPs. Zeta potential was −47.4±5.32 to −50±3.49 mV indicating stable AgNPs. AgNPs up to 2000 mg/kg BW did not cause mortality to rats but caused minimal elevation of serum creatinine and blood urea nitrogen. Low dose was effective in revival of liver enzyme parameters to near normal in all intoxicated groups indicating the curing effects on paracetamol induced liver injury.